Serum lipid and lipoprotein levels in Ghanaians with diabetes mellitus and hypertension. - Nyarko, A. (National Medical Association, 1997)
Both diabetes mellitus and hypertension alter lipid and lipoprotein metabolism and increase the risk of coronary artery disease. We have reported previously on lipid and lipoprotein levels in healthy Ghanaians, and this study deals with the levels of these biochemical parameters in Ghanaians with diabetes mellitus and hypertension. Fasting serum lipoproteins were determined on blood samples drawn from healthy male and female Ghanaians as well as age-matched individuals with either diabetes or hypertension. Cholesterol, high-density lipoprotein cholesterol (HDL-C), triglycerides, and fasting blood glucose were measured. Low-density lipoprotein cholesterol (LDL-C) and very low-density lipoprotein cholesterol (VLDL-C) were derived. Total serum cholesterol levels were 4.43 +/- 0.22 mmol/L and 4.67 +/- 0.26 mmol/L for diabetic males and females, respectively. High-density lipoprotein was 1.55 +/- 0.09 mmol/L and 1.50 +/- 0.09 mmol/L for male and female diabetics, respectively. Lipid and lipoprotein levels in the hypertensive patients did not differ from the above values. The levels of cholesterol and lipoprotein obtained in Ghanaians with hypertension and diabetes mellitus were similar to those of their age-matched healthy controls. These results suggest a reduced risk of coronary artery disease from the atherogenic effects of cholesterol in Ghanaians with diabetes mellitus and hypertension.